Not your usual drug‐drug interactions: Monoclonal antibody–based therapeutics may interact with antiseizure medications. Issue 2 (29th December 2021) - Berman, Erez; Noyman, Iris; Medvedovsky, Mordekhay; Ekstein, Dana; Eyal, Sara
Abstract: Therapeutic monoclonal antibodies (mAbs) have emerged as the fastest growing drug class. As such, mAbs are increasingly being co‐prescribed with other drugs, including antiseizure medications (ASMs). Although mAbs do not share direct targets or mechanisms of disposition with small‐molecule drugs (SMDs), combining therapeutics of both types can increase the risk of adverse effects and treatment failure. The primary goal of this literature review was identifying mAb‐ASM combinations requiring the attention of professionals who are treating patients with epilepsy. Systematic PubMed and Embase searches (1980–2021) were performed for terms relating to mAbs, ASMs, drug interactions, and their combinations. Additional information was obtained from documents from the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA). Evidence was critically appraised ‐ key issues calling for clinicians' consideration and important knowledge gaps were identified, and practice recommendations were developed by a group of pharmacists and epileptologists. The majority of interactions were attributed to the indirect effects of cytokine‐modulating antibodies on drug metabolism. Conversely, strong inhibitors or inducers of drug‐metabolizing enzymes or drug transporters could potentially interact with the cytotoxic payload of antibody‐drug conjugates, and ASMs could alter mAb biodistribution. In addition, mAbs could potentiate adverse ASM effects. Unfortunately, few studies involved ASMs, requiring the formulation of class‐based recommendations. Based on the current literature, most mAb‐ASM interactions do not warrant special precautions. However, specific combinations should preferably be avoided, whereas others require monitoring and potentially adjustment of the ASM doses. Reduced drug efficacy or adverse effects could manifest days to weeks after mAb treatment onset or discontinuation, complicating the implication of drug interactions in potentially deleterious outcomes. Prescribers who treat patients with epilepsy should be familiar with mAb pharmacology to better anticipate potential mAb‐ASM interactions and avoid toxicity, loss of seizure control, or impaired efficacy of mAb treatment.